Faixa de suficiência para a cultura do algodão no centro-oeste do Brasil: II. micronutrientes - Camacho, Marcos Antonio; Natale, William [UNESP]; Barbosa, Jose Carlos [UNESP] (Universidade Federal de Santa Maria (UFSM), 2012)
For to establish the micronutrients sufficiency range for the cotton, was used the method of mathematical chance for nutritional monitory data of three cotton growth locations in the Midwest of the Brazil, evaluating 152 areas. The method of mathematical chance was adequate for to establish cotton micronutrients references values, can be to help parameters were the conventional research cannot to prove in the short time. The micronutrients sufficiency range for productivity of 4000kg ha(-1) were, in the mg kg(-1), 41-89; 4-14; 90-230; 23-100; 25-50, and for 4500kg ha(-1) was 53-83; 4-12; 110-440; 40-60 e 25-50 for B, Cu, Fe, Mn and Zn, respectively. The sufficiency ranges indicated was similar to the existing official recommendations, however, is indicated the approach for to supply the specifics of the systems. The limitations of the method can be minimized with the expansion of the nutritional monitoring system in the cotton crops.
Sufficiency range for cotton cropped in Brazil midwest: II. Micronutrients
Keywords: nutritional evaluation; leaf diagnosis; Gossypium hirsutum r. latifolium